Penerapan Metode Association Rule Terhadap Pola Data Penyakit Pada RSUD Jakarta Menggunakan Algoritma Apriori - Citra Permana Putra; Achmad Rifai; Irmawati Irmawati; Kudiantoro Widianto (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2022)
The hospital is a place to treat patients who come from various regions with various diseases, because lifestyle and the environment play a role in the course of the disease. Some of the problems that arise in dealing with disease include lack of information about the spread of disease and the percentage level of disease spread in the community. One solution to this problem is the application of the association rule method that looks for patterns or relationships between items in a dataset determined by an a priori algorithm that can search historical data to identify data patterns based on previously identified properties. This research method is quantitative data with primary data taken from medical records of Johar Baru Hospital Jakarta. Which then can be obtained an information on what diseases most often appear together in hospitals so that prevention of these diseases can be done. This study aims to find patterns of disease that are developing in the community. The resulting information can then be used by the hospital to maximize the availability of drugs, complete medical equipment, and rooms in the hospital.